IMF Staff Papers, Volume 49, No. 1 - Flood, Robert (IMF Staff Papers; IMF Staff Papers ;, 2002)
This paper presents details of a symposium on forecasting performance I organized under the auspices of the IMF Staff Papers. The assumption that the forecaster's goal is to do as well as possible in predicting the actual outcome is sometimes questionable. ln the context of private sector forecasts, this is because the incentives for forecasters may induce them to herd rather than to reveal their true forecasts. Public sector forecasts may also be distorted, although for different reasons. Forecasts associated with IMF programs, for example, are often the result of negotiations between the IMF staff and the country authorities and are perhaps more accurately viewed as goals, or targets, rather than pure forecasts. The standard theory of time series forecasting involves a variety of components including the choice of an information set, the choice of a cost function, and the evaluation of forecasts in terms of the average costs of the forecast errors. It is generally acknowledged that by including more relevant information in the information set, one should be able to produce better forecasts.